1993
DOI: 10.1017/s0022112093002757
|View full text |Cite
|
Sign up to set email alerts
|

Direct simulations of low-Reynolds-number turbulent flow in a rotating channel

Abstract: Direct numerical simulations of fully developed pressure-driven turbulent flow in a rotating channel have been performed. The unsteady Navier–Stokes equations were written for flow in a constantly rotating frame of reference and solved numerically by means of a finite-difference technique on a 128 × 128 × 128 computational mesh. The Reynolds number, based on the bulk mean velocity Um and the channel half-width h, was about 2900, while the rotation number Ro = 2|Ω|h/Um varied from 0 to 0.5. Without system rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
237
4
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(297 citation statements)
references
References 35 publications
55
237
4
1
Order By: Relevance
“…According to Xun et al [14], the effects of the Coriolis forces on the resolved turbulent stresses and TKE can be further studied using their transport equations. As revealed in the experimental study of Johnston et al [23] and DNS study of Kristoffersen and Andersson [35], the production terms in the transport equations of the resolved turbulent stresses TABLE 4.1: Production terms due to the mean turbulent shear (P ij ) and rotation (G ij ) stresses for a fullydeveloped rotating plane channel flow.…”
Section: Rotation Effect On the Resolved Turbulent Stressesmentioning
confidence: 95%
See 3 more Smart Citations
“…According to Xun et al [14], the effects of the Coriolis forces on the resolved turbulent stresses and TKE can be further studied using their transport equations. As revealed in the experimental study of Johnston et al [23] and DNS study of Kristoffersen and Andersson [35], the production terms in the transport equations of the resolved turbulent stresses TABLE 4.1: Production terms due to the mean turbulent shear (P ij ) and rotation (G ij ) stresses for a fullydeveloped rotating plane channel flow.…”
Section: Rotation Effect On the Resolved Turbulent Stressesmentioning
confidence: 95%
“…The Among the studies of turbulent channel flows subjected to these three types of system rotations, the spanwise rotating turbulent channel flows have been studied extensively through experiments [23,24] and numerical simulations [14,[25][26][27][28][29][30][31][32][33][34][35][36][37]. It is reported that as the rotation number increases, turbulence is gradually enhanced on the pressure side and reduced on the suction side, further resulting in asymmetric distributions in the mean flow and Reynolds stresses [14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. At the same time, large-scale roll cells come forth as a result of the Taylor-Görtler (T-G) instability [14,23,25,35].…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The model has been compared to the DNS results of Kristoffersen & Andersson (1993). The DNS has a turbulent Reynolds number t Re u h / τ = υof 194 where h is the channel half width and u τ = wall dv / dy υ is the shear velocity.…”
Section: Rotating Flowsmentioning
confidence: 99%